A 15kW magnetocaloric proof-of-concept unit: Initial development and first experimental results. (February 2021) - Lionte, Sergiu; Risser, Michel; Muller, Christian
Highlights: Several assembly details of a proof-of-concept magnetic refrigeration prototype are presented. 3 versions of magnetic system have been commented. Magnetic refrigeration experimental results are detailed and analyzed. The prototype has been designed as a 15 kW unit. The results show a Carnot efficiency of 60% and a temperature span of 21.4 K. Abstract: As any innovative development program, magnetic refrigeration still faces many challenges before being widely accepted as an actual replacement technology for cooling. In the last years, more than 50 different types of prototypes of magnetocaloric refrigerators have been presented in literature, with limited cooling power values and/or limited temperature span. This paper presents several assembly details and experimental results of a new proof-of-concept magnetic refrigeration prototype having both a temperature span of more than 20 K and a cooling capacity designed for around 15 kW. It has been made as a part of a pilot project for a large industrial partner to be used for an industrial process. The obtained experimental results have been measured and validated by an exterior independent body. This performance achievement, that we believe to be as the largest rotary magnetic refrigerator ever created, could be a milestone for the future of magnetocaloric chillers.